PENGENDALIAN EMISI DAN LIMBAH DARI INDUSTRI PENYEWAAN ALAT BERAT UNTUK INDUSTRI TAMBANG BATUBARA - Pavita Khansa; Ni Kadek Dian Utami Kartini; Leonardus Alvin Widi Vembrio; Adela Savira Maharani; Sinthia Apriani; I Wayan Koko Suryawan; Nurulbaiti Listyendah Zahra (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
The increasing number of waste-producing industries has led to the emergence of the application of the concept of industrial waste management, including in the heavy equipment rental industry which generates waste in every process of its activity. Not only does it reduce the potential for environmental pollution, this concept can also benefit from a fulfillment of obligations and cost savings. In order to support the achievement of this concept, field studies were carried out to determine the characteristics of the waste produced, as well as literature studies to determine the appropriate measures. After the analysis is carried out, the waste produced is solid waste in the form of used spare parts from the checking and replacement of spare parts, liquid waste in the form of sludge containing detergent, oil and water from the washing process, and CO2 emissions from energy use. Waste minimization is the main effort in industrial waste management and can be achieved by reducing CO2 emissions and applying technology in the form of a gravity separator for wastewater treatment. Processed liquid waste can be reused as clean water so that it can reduce usage and costs for clean water.